Caracterização de proteínas recombinantes de Rickettsia rickettsii para diagnóstico sorológico em suídeos - Loza, Maribel Limachi (2023)
Brazilian Spotted Fever (BSF) is a disease strongly associated with wild boars (Sus scrofa) as its primary hosts, caused by the etiological agent Rickettsia rickettsii. It is an endemic zoonosis primarily transmitted to humans through the bite of ticks of the Amblyomma genus, presenting a high fatality rate (≥ 50%), especially in the southeastern region of the country. Studies have shown that 72.5% of wild boars, 14.1% of hunting dogs, and 14.7% of hunters exhibited seropositivity for at least one species of Rickettsia. The importance of proteins found in the outer membrane of Gram-negative bacteria like R. rickettsii is crucial for physiological functions, virulence, and bacterial resistance, serving as a cellular support. In this study, we evaluated the IgG reactivity of the rOmpA, rPhenAl, and rYJBL proteins using ELISA with a well-characterized wild boar serum panel, with laboratory-confirmed diagnosis through indirect immunofluorescence (IFA). We found a high IgG positivity for recombinant proteins in wild boar serum samples (97.2% for rPhenAl and rYJBL; and 94.4% for rOmpA), indicating these proteins as potential antigen candidates for various immunoassays to be applied in the detection of specific antibodies in suids and other wildlife naturally exposed to Rickettsia sp. and potential immunogens for future research in the development of vaccines against rickettsioses.